Students’ Attitude Towards Learning Mathematics Online - Salada, Abegail P.; Timbal, Antoniette T.; Janiola, Fe R.; Galimpin, Jay L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines the attitude of the non-math major education students on learning mathematics online as a new way of delivering learning during the ongoing pandemic. It determines their attitude in the selected events of instruction. The study make used of descriptive design. Furthermore, the data used in this study were obtained from 50 respondents of Holy Name University who are taking General Education Course - Mathematics online.  Data were collected through self-administered survey questionnaire sent through google form to comply with the existing policies in the midst of pandemic. The responses made by the respondents were collected, tallied, recorded, tabulated, and interpreted with the help of the statistical tools. The result shows that students develop a positive perception in the event of presenting the content. Students got neutral level of perception to the rest of the events of instruction. The result also indicates that there is no significant difference between students’ attitude towards learning mathematics online when grouped according to area of specialization and events of instruction. Moreover, it was concluded that employing various strategies, techniques, and teaching aids in the event of presenting the content develop a positive perception on the students’ attitude towards learning Mathematics. The result proves that the events in instructional method employed in the mathematics classroom show a significant impact on developing students’ attitude towards mathematics learning.